Complete Mitochondrial genome of Eisenia nordenskioldi pallida Malevich, 1956 from Korea, with remarks on the phylogeny of the E. nordenskiodi complex (Megadrili; Lumbricidae) - Csuzdi, Csaba; Koo, Jachoon; Hong, Yong (Zootaxa, 2023)
The Eisenia nordenskioldi (Eisen, 1879) species complex is one of the most widely distributed earthworm taxa in northern Asia, owing to its high morphological and genetic variability. This complex is represented by smaller, slightly pigmented- or unpigmented specimens in the Korean Peninsula. Here, we report the mitogenomes of two Eisenia nordenskioldi cf. pallida specimens, No. 1 and No. 3, which are slightly pigmented and unpigmented, respectively. The total length of the mitogenomes was 15,824 bp and 15,177 bp, respectively, and contained 37 genes, comprising 13 protein-coding genes (PCGs), two rRNA genes, 22 tRNA genes, and a putative non-coding region, as in other earthworms. Nucleotide sequence comparisons of the 37 genes and the predicted protein sequences of 13 PCGs showed 96.6 % and 98.6 % similarity between the two mitogenomes, respectively. A phylogenetic analysis of 33 Crassiclitellata mitogenomes corroborated the monophyly of the Eisenia genus and recovered two highly supported subclades in the E. nordenskioldi species complex. The Korean specimens were the closest to the E. n. pallida L2 specimens collected near the type locality and probably represent the genuine E. nordenskioldi pallida Malevich, 1956.